THE EFFICIENCY OF TOOTH BLEACHING AGENT ACTIVATED WITH ZINC OXIDE ON TOOTH COLOR CHANGE - Klungjaturavet, Nutcha; Srisuparbh, Duangporn; Aimjirakul, Napapa; Padipatvuthikul Didron, Pavinee (Srinakharinwirot University Journal of Sciences and Technology, 2022)
The purpose of this study was to investigate an efficiency of tooth bleaching agents and tooth bleaching agent activated with zinc oxide on tooth color change. Forty premolar teeth were divided into eight groups, each group was treated with PolaOffice® and PolaOffice® activated with 0.1% zinc oxide, using 8,16, 24 and 32 minutes bleaching time. The tooth color was measured before and after bleaching, using the Spectrophotometer. The data was statistically analyzed using two-way ANOVA and Post-Hoc Bonferroni test at 95% level of confidence (α = 0.05). The average tooth color change of the group treated with PolaOffice® for 8, 16, 24 and 32 minutes were 3.02±1.79 4.39±1.19 5.12±1.41 and 5.09±0.27 respectively, whereas the average tooth color change of the group treated with PolaOffice® activated with zinc oxide for 8, 16, 24 and 32 minutes were 4.43±1.27 4.99±1.35 7.49±1.09, and 7.02±0.29 respectively. The statistical analysis showed that the tooth color change of groups treated with PolaOffice® activated with zinc oxide for 24 and 32 minutes were significantly higher than the group treated with PolaOffice® for the same duration. In conclusion, PolaOffice® activated with 0.1% zinc oxide can significantly improve the tooth color change when using 24 and 32 minutes bleaching time.